The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1001/archsurg.2007.69
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide

Abstract: This study confirms the relationship between BNP level elevation and severity of sepsis independent of congestive heart failure. It also supports the utility of BNP level as a marker for mortality in septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 34 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…SubP gave higher specificity (83%) and sensitivity (80%) than NT-proBNP which was reported as an early marker candidate for the diagnosis of AMI patients in many groups. 10,21,27 From above results, we suggested SubP and NPY as early diagnostic biomarkers for AMI patients. The combination of two peptides analysis will give a chance to find for AMI patients in early stage.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…SubP gave higher specificity (83%) and sensitivity (80%) than NT-proBNP which was reported as an early marker candidate for the diagnosis of AMI patients in many groups. 10,21,27 From above results, we suggested SubP and NPY as early diagnostic biomarkers for AMI patients. The combination of two peptides analysis will give a chance to find for AMI patients in early stage.…”
Section: Resultsmentioning
confidence: 72%
“…21 Similar peptide markers, including atrial natriuretic peptide, B-type natriuretic peptide (BNP), and C-type natriuretic peptide have been studied extensively. 22 Currently, BNP, which is a peptide hormone released from cardiomyocytes upon a mechanical stretch, has been recommended for clinical use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These median values were similar to those of the 51 patients in the study who had acute heart failure with BNP 581 pg/ml (6-1,300) and NT-proBNP 4,300 pg/ml (126-70,000). Kandil et al [66] also found that patients with septic shock on admission had significantly higher BNP levels compared to patients in early sepsis without a final diagnosis or a control group. Interestingly, BNP levels were not significantly elevated in patients with early sepsis.…”
Section: Elevated Nps In Other Disease Statesmentioning
confidence: 93%